2005
DOI: 10.1051/vetres:2004052
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Bartonella sp. in questing adult and nymphal Ixodes ricinus ticks from France and co-infection with Borrelia burgdorferi sensu lato and Babesia sp.

Abstract: -Ticks are known vectors for a wide range of pathogenic microorganisms. Their role in the transmission of some others is so far only suspected. Ticks can transmit multiple pathogens, however, little is known about the co-existence of these pathogens within questing ticks. We looked for the presence of DNA from three micro-organisms, Bartonella sp., Borrelia burgdorferi sensu lato and Babesia sp. which are known or suspected tick-borne pathogens, using a cohort of 92 questing Ixodes ricinus ticks collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 41 publications
6
64
2
1
Order By: Relevance
“…The presence of Bartonella spp. has been confirmed in ticks Ixodes pacificus in California (Chang et al, 2001) and Bartonella henselae -in I. ricinus ticks in Italy and Denmark (Schouls et al, 1999;Sanogo et al, 2003, Halos et al, 2005.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of Bartonella spp. has been confirmed in ticks Ixodes pacificus in California (Chang et al, 2001) and Bartonella henselae -in I. ricinus ticks in Italy and Denmark (Schouls et al, 1999;Sanogo et al, 2003, Halos et al, 2005.…”
Section: Discussionmentioning
confidence: 96%
“…DNA was detected in questing and engorged nymphs and adults Ixodes spp. collected in North America, Europe, and Asia (13,(18)(19)(20)(21)(22)(23)(24)(25)(26). If one considers that ixodid ticks feed only once per stage, Bartonella spp.…”
mentioning
confidence: 99%
“…with known tick-borne pathogens such as B. burgdorferi sensu lato, A. phagocytophilum, or Babesia spp. is not a rare event in ticks and hosts (13,19,24,27). A study conducted in a veterinary hospital in the United States (California) demonstrated that all dogs with endocarditis and infected with Bartonella spp.…”
mentioning
confidence: 99%
“…1 Because idiopathic macular holes rarely occur before the age of 55 years 3 Falthough we could not dispute the idiopathic origin of our caseFwe speculate that vitreous inflammation causing vitreous gel shrinkage and tangential traction in combination with macular oedema could cause a macular hole. The present case indicates that pars plana vitrectomy combined with ILM peeling might lead Sir, Neuroretinitis secondary to concurrent infection with cat scratch disease and lyme disease Neuroretinitis is an infectious or inflammatory process of the optic nerve characterized by optic disc oedema and macular star.…”
Section: Commentsmentioning
confidence: 72%
“…Recently, however, Bartonella species have been isolated in the I. ricinus tick with concurrent presence of B. burgdorferi species. 2,3 Identification of coinfected ticks suggests a possible new transmission mechanism of CSD and LD and should be considered when evaluating a patient with neuroretinitis.…”
Section: Commentmentioning
confidence: 99%